2018
DOI: 10.1002/joc.5682
|View full text |Cite
|
Sign up to set email alerts
|

Decadal changes in summer precipitation over arid northwest China and associated atmospheric circulations

Abstract: The precipitation over arid regions may be low, but its environmental impacts can be very dramatic. The decadal variability in precipitation can also effectively disturb climatic environmental regimes. To advance the understanding of precipitation variability over arid regions, this paper focuses on decadal variability in summer precipitation over arid northwest China and its associated atmospheric circulations, using observation-based data and atmospheric reanalysis during the period 1961-2016. The results sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
16
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 34 publications
(18 citation statements)
references
References 49 publications
2
16
0
Order By: Relevance
“…In contrast, water vapour transport into the ENWC from its southern and northern boundaries shows an interannual fluctuation, without a significant decadal trend (Figure c,d). Moreover, the regional net water vapour budget is mainly derived from meridional water vapour transport, while zonal water vapour transport is a negative contributor (Figure ), illustrating the important role played by the northward transportation of water vapour from low‐latitude oceans and seas (Mariotti et al ., ; Zhao et al ., ; Li and Ma, ). In addition, the net water vapour budgets fluctuated around zero during the period from 1980 to 2014.…”
Section: Resultsmentioning
confidence: 98%
“…In contrast, water vapour transport into the ENWC from its southern and northern boundaries shows an interannual fluctuation, without a significant decadal trend (Figure c,d). Moreover, the regional net water vapour budget is mainly derived from meridional water vapour transport, while zonal water vapour transport is a negative contributor (Figure ), illustrating the important role played by the northward transportation of water vapour from low‐latitude oceans and seas (Mariotti et al ., ; Zhao et al ., ; Li and Ma, ). In addition, the net water vapour budgets fluctuated around zero during the period from 1980 to 2014.…”
Section: Resultsmentioning
confidence: 98%
“…Observations show that precipitation has been increasing continuously since the past half century in NWC (Zhai et al ., 2005; Shi et al ., 2007). Many studies have been performed to explore the possible factors for this climate change (Zhou and Huang, 2010; Chen and Huang, 2012; Huang et al ., 2015; Zhou and Wu, 2015; Li et al ., 2016; Li and Ma, 2018; Wu et al ., 2019; Shang et al ., 2020). Zhao et al .…”
Section: Introductionmentioning
confidence: 99%
“…Observations show that precipitation has been increasing continuously since the past half century in NWC (Zhai et al, 2005;Shi et al, 2007). Many studies have been performed to explore the possible factors for this climate change (Zhou and Huang, 2010;Chen and Huang, 2012;Huang et al, 2015;Zhou and Wu, 2015;Li et al, 2016;Li and Ma, 2018;Wu et al, 2019;Shang et al, 2020). Zhao et al (2014) revealed an indirect but important impact of the South Asian summer monsoon on summer rainfall increases over the Tarim Basin by inducing middle and upper tropospheric cooling over central Asia.…”
mentioning
confidence: 99%
“…The significant regional variability of heavy rainfall climatology has also been found in the United States (Hitchens et al ., 2013), India (Deshpande et al ., 2012), Germany (Zolina et al ., 2008) and elsewhere. The strengthening of the West Pacific Subtropical High (WPSH) and the North America Subtropical High (NASH) after the mid‐1980s was considered as an important factor for the increasing trend of rainfall in Northwest China (Li et al ., 2016; Zhang et al ., 2017; Li and Ma, 2018), with higher wetting trends over mountainous regions (Wang et al ., 2019). Studies on the summer heavy rainfall over the YRB during 1960–2011 indicated that most rainfall indices decreased, but the maximum daily rainfall increased in most locations (Gao and Wang, 2017), which resulted in increases in drought or flood disasters.…”
Section: Introductionmentioning
confidence: 99%